Lohmannella septemsetosa Bartsch 2005 - Abé, Hiroshi (Zenodo, 2021)
Lohmannella septemsetosa Bartsch, 2005 Diagnosis. One cornea present. Ds-2 and Ds-3 on membranous cuticle. Two dorsal setae on PE. Female with 17 Pgs and 8 Sgs. Male with 54 Pgs and 8 Sgs. Tr I–IV with 1-1-1-1 setae; Bf I–IV with 3-3-3-3 setae; Tf I–IV with 9-9-6-4 setae; Gn I–IV with 9-9-5-5 setae, 4-4-0-2 Bp setae; Tb I–IV with 14-13-10-10 setae, 7-4-2-3 Bp setae; Ta I–IV with 3-3-4-3 dorsal setae, 2-2-3-2 Bp setae. Lc I with unidentate accessory process. Idiosoma length 447 in female, 410 in male (holotype), 290 in DN, 202 in LV. Idiosoma width 302 in male holotype, 167 in LV. Gnathosoma length 317 in female, 284 in male holotype, 116 in DN, 119 in LV. Gnathosoma width 107 in male holotype. Ratio of gnathosoma to idiosoma 0.69 in male holotype, 0.71 in female, 0.40 in DN. Ratio of P-2 to P-1 4.20. Remarks. The characteristics of this species are: Glps with large alveoli and 7 ventral Bp setae on Tb I. Male, female, DN, and LV are known. Habitat. Littoral zone: Algal tufts with sediment, 30 cm below water edge, 50 cm depth. Distribution. Indian Ocean: Lucky Bay, Cape Le Grand, Duke of Orleans Bay (near Esperance) [Australia]. References. Bartsch (2005b, 2007a). Depository. WAMP. : Published as part of Abé, Hiroshi, 2021, Taxonomic review of the subfamily Lohmannellinae (Acari: Trombidiformes Halacaridae) with morphological comparisons among genera, pp. 201-255 in Zootaxa 4980 (2) on pages 219-220, DOI: 10.11646/zootaxa.4980.2.1, http://zenodo.org/record/4888860 : {"references": ["Bartsch, I. (2005 b) Halacaridae from the depths of Western Antarctica (Arachnida: Acari). Senckenbergiana biologica, 85, 31 - 41.", "Bartsch, I. (2007 a) Halacarid mites (Acari: Halacaridae) from Esperance, Western Australia: Notes on taxonomy and faunal distribution of non-Copidognathinae. Records of the Western Australian Museum, 23, 359 - 392."]}